Supporting effective alternative access for individuals with physical disabilities: state of the science, emerging technologies, and future research directions. - Koester, Heidi; Koch Fager, Susan; Gormley, Jessica; Jakobs, Erik; Johnsen, Kelli; Brumberg, Jon (AAC: Augmentative & Alternative Communication, 2025)
Alternative access methods accommodate an individual's specific physical disability, by adjusting the typical keyboard/mouse/touchscreen interface or using an alternative interface such as head controls, eye trackers, or switches. Ideally, they allow for efficient and comfortable use of any computing device, such as laptops, tablets, and smartphones. This paper reviews the literature to address two main questions: how well do existing access methods meet users' needs? And what is the best way to choose the "right" access method(s) for a given individual? We report on typing speeds for various access methods across 57 studies, as well as experimental multimodal access methods across 34 papers. Results support the intuitive understanding that the access method affects the end user's experience and productivity. We also reviewed 33 papers and resources related to alternative access assessment and service provision. Existing evidence remains emerging and suggests that use of a systematic, user-centered approach to alternative access assessment may reap significant benefits, including better team performance and improved user satisfaction. Yet although many alternative access assessment resources are available, providers may not always use them. While today's alternative access methods can be an impactful means of enabling participation for people with physical disabilities, there is room for improvement, both in the access methods themselves, as well as their associated service provision and support. To identify and implement these improvements, the field needs research and development that is fully inclusive of people with disabilities in all phases of the work. We list some additional priorities for future work.